Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1128/aem.02507-20
|View full text |Cite
|
Sign up to set email alerts
|

Cry75Aa (Mpp75Aa) Insecticidal Proteins for Controlling the Western Corn Rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), Isolated from the Insect-Pathogenic Bacterium Brevibacillus laterosporus

Abstract: This study describes three closely related proteins, cloned from Brevibacillus laterosporus strains, that are lethal upon feeding to Diabrotica virgifera virgifera LeConte, the western corn rootworm (WCR). Mpp75Aa1, Mpp75Aa2 and Mpp75Aa3 were toxic to WCR larvae when fed purified protein. Transgenic plants expressing each mMpp75Aa protein were protected from feeding damage and showed significant reduction in adult emergence from infested plants by both susceptible and Cry3Bb1 and Cry34Ab1/Cry35Ab1-resistant WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Mpp75Aa1.1 (formerly known as Cry75Aa1.1), discovered by mining the genome of Brevibacillus laterosporus , provides effective control of WCR larvae when expressed in transgenic maize [ 7 ]. Furthermore, Mpp75Aa1.1 exhibits significant activity toward WCR that are resistant to Cry3Bb1 and Gpp34Ab1/Tpp35Ab1 (formerly known as Cry34Ab1/Cry35Ab1) [ 7 ], suggesting a distinct receptor specificity in WCR compared to Cry3Bb1 and Gpp34Ab1/Tpp35Ab1. Bioinformatic analysis identified that Mpp75Aa1.1 belongs to the aerolysin-like superfamily of bacterial beta-pore forming proteins (β-PFPs) found across all kingdoms of life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mpp75Aa1.1 (formerly known as Cry75Aa1.1), discovered by mining the genome of Brevibacillus laterosporus , provides effective control of WCR larvae when expressed in transgenic maize [ 7 ]. Furthermore, Mpp75Aa1.1 exhibits significant activity toward WCR that are resistant to Cry3Bb1 and Gpp34Ab1/Tpp35Ab1 (formerly known as Cry34Ab1/Cry35Ab1) [ 7 ], suggesting a distinct receptor specificity in WCR compared to Cry3Bb1 and Gpp34Ab1/Tpp35Ab1. Bioinformatic analysis identified that Mpp75Aa1.1 belongs to the aerolysin-like superfamily of bacterial beta-pore forming proteins (β-PFPs) found across all kingdoms of life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two strains of B. laterosporus were isolated following methods previously described (11). The EG4227 strain was isolated from grain dust while the BOD strain was isolated from the powder of a commercially available probiotic capsule.…”
Section: Assessment Of the Presence Of Mpp75a In B Laterosporusmentioning
confidence: 99%
“…The proteins were electro-transferred from the gel to 0.2 M nitrocellulose membrane using Bio-Rad Turbo Blot TM device for 7 minutes. The membrane was probed with a primary anti-mMpp75Aa2 (mature form of Mpp75Aa2, (11)) polyclonal antibody diluted at 1 g/ml in the 1X phosphate buffered saline with 0.1% Tween ® 20 with PBST + 2% non-fat milk (NFMK) overnight (~12 hours at 4 o C). The membrane was washed 3 times with 1X PBST to remove primary antibody.…”
Section: Assessment Of the Presence Of Mpp75a In B Laterosporusmentioning
confidence: 99%
See 1 more Smart Citation
“…These germplasm will be widely planted for the first time in 2022. Bayer also recently discovered an additional Bt protein [194] and a protein from Brevibacillus laterosporus [195], each with strong activity against western corn rootworm larvae and no cross resistance to current rootworm toxins. Corteva has a new transgenic maize line producing a toxin derived from Pseudomonas chlororaphis pyramided with dsRNA available [151], but the feasibility for large scale application has yet to be evaluated.…”
Section: Using Pathogenic Microbials To Reduce Wcr Populationsmentioning
confidence: 99%